HAK NAFKAH SEORANG ANAK SETELAH TERJADINYA PERCERAIAN KEDUA ORANG TUANYA - Rofiq, Nur; Gunawan, Nama Frisca Choirunisa; Syafila, Apriliana Ratih; Sari, Dahlia Apriliana Mekar; Putri, Angelica Erviana; Novalia, Naila; Khayati, Siwi Nur; Putri, Aninditya Eka Syahdrania; Bily, Muhammad Yusuf Arda; Hajdi, Kuswan (Wahana Islamika Jurnal Studi Keislaman, 2024)
Marriage is a sacred bond between a man and a woman which completes worship according to the commands of Allah and the Messenger of Allah which can avoid adultery. The purpose of writing is to determine a child's maintenance rights after the divorce of his parents. The research method used is a normative juridical approach with data analysis techniques using descriptive qualitative. The research results state that based on the Qur'an, Hadith, Marriage Law and the Compilation of Islamic Law (KHI) that child support is a father's obligation. This is confirmed in Appendix SEMA 3/2018 (p. 14) and in Article 197 HIR (1st paragraph). So, after a divorce, children will receive their rights, which are called hadhanah living, namely the costs of caring for, caring for and educating the child until they reach adulthood.